Livelihoods and Welfare Impacts of Forest Comanagement - Linda Chinangwa; Andrew S. Pullin; Neal Hockley (International Journal of Forestry Research)
Comanagement programmes are gaining popularity among governments as one way of improving rural livelihoods. However, evidence of their effects on the livelihoods and welfare remains unclear. We used the sustainable livelihoods framework and stated preference techniques to assess the livelihoods and welfare impacts of forest comanagement on 213 households in Zomba and Ntchisi districts. The results show that approximately 63% of respondents perceive that, overall, comanagement has had no impact on their livelihoods. However, the programme is enhancing financial capital by introducing externally subsidised income generating activities and human and social capital among some community members through training programmes. A majority of households (80%) are willing to pay annual membership fees to participate in the programme (mean = 812 Malawi Kwacha), because of perceived potential future benefits. Education, gender of the household head, a positive perception of current livelihoods benefits, and a position on the committee increase household willingness to pay membership fees. However, the positive willingness to pay despite the negative perception of overall livelihoods impacts may also demonstrate the weaknesses of relying on stated preference surveys alone in estimating welfare effects.